Exploring quantitative trait nucleotides associated with response to yam mosaic virus severity and tuber yield traits in Dioscorea praehensilis Benth. germplasm via genome-wide association scanning - Adewumi, A.S.; Adejumobi, I.I.; Opoku, V.A.; Asare, P.A.; Adu, M.O.; Taah, K.J.; Stanley, A.E.; Olatunde, T.E.; Afutu, E.; Akaba, S.; Mushoriwa, H.; Agre, A.P. (Frontiers Media, 2024)
Yam production in sub-Saharan African countries faces challenges due to susceptibility to yam mosaic virus (YMV) disease, leading to significant yield losses. Dioscorea praehensilis, a semicultivated yam species known for its high yield and resistance to YMV, can be utilized as a new variety and a gene source to enhance tuber yield and YMV resistance of White Guinea yam.Investigating the genetic basis of tuber yield-related traits and YMV resistance in D. praehensilis through association mapping will facilitate the traits discovery and deployment into the yam breeding program.A total of 132 D. praehensilis genotypes were evaluated in 2022 and 2023 seasons for tuber yield per plant, tuber size ratio and for mosaic virus severity response. The genotypes were sequenced using SNP markers generated from Diversity Array Technology Platform. The trait association analysis was conducted using mixed linear model implemented in GWASpoly package followed for putative genes analysis.Population structure and phylogeny analyses using 4,525 single nucleotide polymorphism (SNP) markers grouped the 132 D. praehensilis genotypes into three clusters. Using multiple gene action models which include dominant, additive, and general models, 27 SNP markers were significantly identified to be associated with the tuber yield, tuber size ratio and yam mosaic virus severity. Of these 27 SNPs, we identified three and two SNP markers for tuber yield and yam mosaic virus severity, respectively as stable markers across years. Using gene annotation, we identified 10 putative genes such as Serine/threonine-/ dual specificity protein kinase, catalytic domain involved in starch biosynthesis and Ribosomal protein L5 involved in defense signaling against virus diseases. The marker effect revealed that alleles CC and TT were associated with high tuber yield, while AA and AC were linked with low tuber yield. For YMV severity response, alleles CC and CT were linked with low YMV severity, while TT was associated high YMV severity prediction.The results of this study offer valuable insights into comprehending the functional networks involved in developing strategies to enhance tuber yield and resistance to yam mosaic virus in Dioscorea spp.